Severe invasive methicillin-resistant S. aureus (USA300 clone) infection in an Italian adolescent - Piero Valentini; Donatella Angelone; Francesca Crea; Annalisa Pantosti (Clinical Management Issues, 2009)
This report describes an uncommon presentation of invasive community-acquired methicillin-resistant S. aureus (CA-MRSA) infection in an immunocompetent adolescent without any other risk factor, characterized by septicaemia, meningitis, necrotising pneumonia and deep venous thrombosis (DVT). Successful treatment was performed with linezolid, rifampicin and low-molecular-weight heparin (LMWH). MRSA molecular typing revealed the presence of Panton-Valentine leukocidin (PVL) gene, and a genetic background identical to USA300 clone, an emerging aggressive CA-MRSA strain in USA and Europe.